Stunting and associated factors among primary school children in Ethiopia: School-based cross-sectional study - Dirshaye Argaw; Robel Hussen Kabthymer; Tsion Endale; Aregahegn Wudneh; Meiraf Daniel Meshesha; Jarsso Tadesse Hirbu; Yesuneh Bayisa; Lulu Abebe; Ruth Tilahun; Saron Aregawi; Mengistu Lodebo Funga; Tilahun Wodaynew; et al. (International Journal of Africa Nursing Sciences, 2022)
Background: Stunting is a common type of undernutrition in schoolchildren, and it has a significant negative impact on academic performance. Stunting refers to a child who is too short for their age. It is the result of chronic or recurring malnutrition. Stunting can have far-reaching consequences that last a lifetime. Malnutrition is still a major public health concern in developing countries, including Ethiopia, with an estimated 118 million people going hungry by 2020. Therefore, this study was intended to assess the prevalence and associated factors of stunting among primary school children. Methods: A cross-sectional school-based study was conducted in Gedeo Zone, South Ethiopia. A multistage sampling technique was used to get a total of 500 study participants from May 1 to June 30, 2021. Data was collected by using face-to-face interviews with structured questionnaires. It was entered into Epi Data version 3.1 and exported to SPSS version 23 for analysis. Variables with a p value of 0.25 in bivariate analysis were fitted to multivariable analysis. A multivariable logistic regression model with a 95% confidence interval and a P-Value of 0.05 was used. Results: The study found that 203 (40.6%) of the 500 primary students enrolled were stunted (95% CI: 17–47). Stunting was significantly associated with educational status [AOR 2.49 (95%CI (1.23, 4.06)], dietary diversity [AOR 2.0, (95%CI (1.64, 3.54)], child age [AOR 3.48, (95%CI (2.04, 6.16)], family size [AOR 2.18, (95%CI (2.06, 4.49)], and family type [AOR 2.94, (95%CI (1.84, 4.72)]. Conclusion: More than one-third of elementary school children were stunted. Implementing school health and nutrition initiatives to improve the nutritional status of school-age children in the study area is critical, as is considering a strategy to improve children's wellbeing through cross-cutting child wellbeing strategies, with a special focus on vulnerable children. It should be considered to empower vulnerable families who are at risk of having a child with stunting to improve children's home environments.